Long-term potentiation of magnonic synapses by photocontrolled spin current mimicked in reentrant spin-glass garnet ferrite Lu3Fe5−2xCoxSixO12 thin films. (16th March 2015) - Adachi, Masaki; Seki, Munetoshi; Yamahara, Hiroyasu; Nasu, Hidekazu; Tabata, Hitoshi
Abstract: (Co, Si)-cosubstituted Lu3 Fe5 O12 (Lu3 Fe5−2 x Co x Si x O12 ; 0.00 ≤ x ≤ 1.00) thin films were grown on Y3 Al5 O12 (001) substrates by pulsed laser deposition. Reentrant spin-glass behavior was observed and its robustness against external magnetic fields was improved by increasing the Co–Si content. In contrast, the spectral linewidth of ferromagnetic resonance was broadened by increasing the Co–Si content, which indicates that the Lu3 Fe4.8 Co0.1 Si0.1 O12 thin film is an optimal spin-glass spin-wave conductor. The spin pumping voltage of Lu3 Fe4.8 Co0.1 Si0.1 O12 exhibited short-term plasticity with photoinduced magnetic anisotropy and long-term potentiation with the photomemory effect, which mimicked the pre- and postsynaptic potentials of biological systems.